Interdisciplinary and Inter-Institutional Differences in Learning Preferences among Malaysian and Health Sciences Students. - Wong, Rebecca S.Y; Siow, Heng Loke; Vinoth, Kumarasamy; Nazrila Shaherah, Fadhlullah Suhaimi (2017)
The learner-centred approach in medical and health sciences education makes the study of learning preferences relevant and important. This study aimed to investigate the interdisciplinary, interinstitutional, gender and racial differences in the preferred learning styles among Malaysian medical and health sciences students in three Malaysian universities, namely SEGi University (SEGi), University of Malaya (UM) and Universiti Tunku Abdul Rahman (UTAR). It also investigated the differences in the preferred learning styles of these students between high achievers and non-high achievers. Methods: This cross-sectional study was carried out on medical and health sciences students from three Malaysian universities following the approval of the Research and Ethics Committee, SEGi University. Purposive sampling was used and the preferred learning styles were assessed using the VARK questionnaire. The questionnaire was validated prior to its use. Three disciplines (medicine, pharmacy and dentistry) were chosen based on their entry criteria and some similarities in their course structure. The three participating universities were Malaysian universities with a home-grown undergraduate entry medical program and students from a diverse cultural and socioeconomic background. The data were analysed using the Statistical Package for the Social Sciences (SPSS) software, version 22. VARK subscale scores were expressed as mean±standard deviation. Comparisons of the means were carried out using t-test or ANOVA. A p value of <0.05 was considered as statistically significant, and <0.001 as highly significant. Results: Both statistically significant interdisciplinary and inter-institutional differences in learning preferences were observed. Out of the 337 students, a majority of the participants were unimodal learners (n=263, 78.04%). The most common type of learners was the reading/writing type (n=92, 27.30%) while the kinesthetic subscale (M=6.98, SD=2.85) had the highest mean score. Female students (M=6.86, SD=2.86) scored significantly higher than male students (M=6.08, SD=2.41; t(249), p=0.014) in the auditory subscale, whereas Chinese students (M=5.87, SD=2.65) scored significantly higher than Malay students (M=4.70, SD=2.87; p=0.04) in the visual subscale. However, the mean VARK subscale scores did not differ significantly between high achievers and non-high achievers (p>0.05). Conclusion: This study gives an insight into the learner characteristics of more than one medical school in Malaysia. Such multi-institutional studies are lacking in the published literature and this study gives a better representation of the current situation in the learning preferences among medical students in Malaysia.